Peningkatan Literasi Keuangan dalam Mewujudkan Pengelolaan Keuangan Keluarga yang Baik pada Masyarakat Desa Raoda Kolaka Utara - Fitri Kumalasari; Niar Astaginy; Agus Zul Bay; Almansyah Rundu Wonua; Ismanto Ismanto (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Good financial management is essential for the financial well-being of a family. Financial management is heavily reliant on the financial literacy of the family. Financial literacy will assist families in understanding risk, making good investment decisions, and developing disciplined money management practises. The Raoda village community does not yet have a solid grasp on financial literacy. The majority of people are still unable to plan investments and manage financial risks. This project aims to educate and enhance financial literacy in the Raoda Village community on Family Financial Management. The activities began with observation and cooperation with the village government, followed by the production of activity plans, materials, and aid in the preparation of plans and assessments. Following completion of this programme, it was discovered that the family was capable of making their own plans and managing simple family finances. There were some participants in this activity who, due to their education level and age, were unable to properly organise their family finances. Aside from these variables, the bulk of women's labour as housewives is the most important determining factor. Several factors contribute to the lack of financial literacy in setting plans and planning for strong financial governance.